ME/CFS Causes, Clinical Features and Diagnosis - Pheby, Derek F. H.; Friedman, Kenneth; Murovska, Modra; Zalewski, Pawel (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
"ME/CFS: Causes, Clinical Features and Diagnosis" addresses the early stages of ME/CFS and underlying predisposing factors. It considers the plight of the individual patient, and also the impact of the illness on society as a whole, which is considerable, in terms of both costs and social disruption. Patients and their families and carers frequently experience discrimination and difficulties accessing care. This volume will be of particular interest to those undertaking scientific research and those providing clinical care for ME/CFS patients, as well as to social policy analysts, policy makers and governments, and specialists in social research and medical education. There is a major focus on shortcomings in terms of medical education, resulting in considerable gaps in knowledge and understanding of the condition among many doctors. International comparisons indicate that these problems are encountered in many countries. This is particularly topical at a time when Long Covid-19 has moved post-viral syndromes to the forefront of the political agenda, and confronted society with new challenges in this area on a hitherto unprecedented scale. The volume addresses the many points of similarity between Long Covid-19 and ME/CFS. Mitigation of the illness is also addressed, through espousal of a more patient-centred approach to care, and through consideration of the scope for prevention. Sixty-nine authors from seventeen European countries, and from Canada and the USA have contributed to this volume, which is a truly international collaboration.